6 6 6 6 6 6
Find the 6 th last digit from the right of the decimal representation of the above number.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is not clear to me why you wanted to find 2 6 x ( m o d 5 6 ) . You can just find x ( m o d 5 6 ) and x ( m o d 2 6 ) , and then apply Chinese Remainder Theorem.
Log in to reply
Calvin, can you show a solution to this using CRT?
Yes that is possible as well, its just that I prefer to approach all modulo arithmetic questions using this method. :)
can we solve through shortcut method? i couldn't understand...
Why do you even show this: ϕ ( 5 n . 2 k ) = 5 n − 1 . 2 k + 1 ? You never actually use it because your iteration step prevents you from getting to that.
There might be a flaw in the iteration step (**), even though it does not change the result. You claim essentially:
x m o d 2 2 ≡ 0 ⇒ ( x m o d 5 k − 1 ⋅ 2 2 ) ≡ ( x m o d 5 k − 1 ) m o d 5 k
Counterexample: x = 2 8 ; k = 2 yields 8 ≡ 3 m o d 2 5
However, for the tetration x = k − 1 6 the claim holds - but to see that, you need to know 6 5 k − 1 ≡ 1 m o d 5 k , 5 k − 1 < 2 2 ⋅ 5 k − 1 = ϕ ( 5 k ) , k ≥ 1
is another, even shorter cycle length than the worst case estimate we get with Euler's Totient. If we know that, we can safely ignore the extra factors of 4, because they will not matter anyway: The shorter cycle will just repeat the first 5 k − 1 values.
For the relevant k ≤ 6 , we really have this shorter cycle length (checked via program) and it actually is the minimum cycle length each time! So in this particular problem it does not matter that we ignore the factors of 4 - but how can we know we may do that, without resorting to brute force?
not at all
To get the sixth digit on the right of the tetration 6 6 , we need all of the last six digits. We can extract them using r 6 ≡ 6 6 m o d 1 0 6 Instead of doing that directly, it will be more helpful to prove the following solution to a (slightly) more general problem: r k ≡ k 6 m o d 2 i ⋅ 5 k ⇔ r k r k ≡ 0 m o d 2 i ≡ 6 r k − 1 m o d 5 k r k − 1 ≡ k − 1 6 m o d 2 2 ⋅ 5 k − 1 , i , k ∈ N , 2 ≤ i ≤ k ( 1 ) We notice: The congruence we have to solve for r k − 1 is of the same form as before, but the tetration is smaller!
Proof: We want to reduce the enormous exponential k 6 with Euler's Theorem . Sadly, g cd ( 6 , 2 i ⋅ 5 k ) = 2 , so we cannot use it directly! Instead we work with the Chinese Remainder Theorem, as g cd ( 2 i , 5 k ) = 1 : r k ≡ k 6 m o d 2 i ⋅ 5 k ⇔ r k r k ≡ k 6 m o d 2 i ≡ k 6 m o d 5 k ∣ ∣ k − 1 6 ≥ k ≥ i ⇒ g cd ( k 6 , 2 i ⋅ 5 k ) = g cd ( 6 k − 1 6 , 2 i ⋅ 5 k ) = 2 i The first congruence is simply zero: We already know 2 i is a factor of k 6 . The second congurence is harder, but now we can use Euler's Theorem as g cd ( 6 , 5 k ) = 1 . The idea is to write the exponent k − 1 6 in terms of ϕ ( 5 k ) = 2 2 ⋅ 5 k − 1 : k − 1 6 = ! c ϕ ( 5 k ) + r k − 1 , c ∈ Z ⇒ r k ≡ k 6 ≡ 6 k − 1 6 ≡ 6 c ϕ ( 5 k ) ⋅ 6 r k − 1 ≡ 1 c ⋅ 6 r k − 1 ≡ 6 r k − 1 m o d 5 k ■
To solve the original problem, we factor 1 0 6 = 2 6 ⋅ 5 6 and use (1) repeatedly to get down to 1 6 = 6 : r 6 r 6 ≡ 0 m o d 2 6 ≡ 6 r 5 m o d 5 6 r k r k ≡ 0 m o d 2 2 ≡ 6 r k − 1 m o d 5 k k ∈ { 2 ; … ; 5 } r 1 ≡ 6 m o d 2 0 Though it is tedious, we can solve these six systems of congruences by hand using the power method (see reply), starting with r 1 and ending with r 6 . The results are listed below, the sixth digit on the right of r 6 is the answer: k r k 1 6 2 5 6 3 1 5 6 4 1 1 5 6 5 1 1 5 6 6 2 3 8 6 5 6
Rem.: As an example, we will calculate r 3 using the power method. We write the exponent r 2 in powers of 2: r 3 ≡ 6 r 2 ≡ 6 5 6 ≡ 6 8 ⋅ 6 1 6 ⋅ 6 3 2 ( ∗ ) ≡ ( − 9 ) ⋅ 8 1 ⋅ 6 1 ≡ ( − 9 ) ⋅ 4 9 4 1 ≡ ( − 9 ) ⋅ ( − 5 9 ) ≡ 3 1 m o d 5 3 We get the powers 6 2 k by squaring repeatedly - that's why it's called the power method: 6 4 6 8 ≡ 3 6 2 ≡ 1 2 9 6 ≡ 4 6 m o d 5 3 , ≡ 4 6 2 ≡ 2 1 1 6 ≡ − 9 m o d 5 3 , 6 1 6 6 3 2 ≡ ( − 9 ) 2 ≡ 8 1 m o d 5 3 ≡ 8 1 2 ≡ 6 5 6 1 ≡ 6 1 m o d 5 3 ( ∗ ) Finally we combine the result with the other congruence for r 3 to build a diophantine equation: r 3 r 3 ≡ 0 m o d 2 2 ≡ 3 1 m o d 5 3 ⇔ r 3 r 3 = 4 x = 3 1 + 1 2 5 y } 3 1 = 4 x − 1 2 5 y , x , y ∈ Z Using Euclid's Algorithm, we find the solution. We shift the index k = k ′ + 4 to get to smaller numbers: ( x y ) = ( − 3 1 − 1 1 2 5 4 ) ( 3 1 k ) ⇒ r 3 = 4 x = − 4 ⋅ 9 6 1 + 1 0 0 0 k = 1 5 6 + 1 0 0 0 k ′
Have fun with r 4 , r 5 , r 6 !
Problem Loading...
Note Loading...
Set Loading...
The solution to the problem is x where 6 6 6 6 6 6 ≡ x m o d 1 0 6 . We see that g cd ( 6 6 6 6 6 6 , 1 0 6 ) = 1 . Thus, we reduce this modulo by dividing each term by 2 6 as proven on a separate note. With that, we obtain 2 6 6 6 6 6 6 6 ≡ 2 6 x m o d 5 6 . To solve this, we shall apply Euler's totient function repeatedly such that ϕ ( 5 n ) = 5 n − 1 . 2 2 and ϕ ( 5 n . 2 k ) = 5 n − 1 . 2 k + 1 . Hence: 2 6 6 6 6 6 6 6 ≡ 2 6 x m o d 5 6 2 6 6 6 6 6 6 6 ( m o d 5 5 . 2 2 ) ≡ 2 6 x m o d 5 6 ** Now, observe the index of 6 , which is 6 6 6 6 6 ≡ y m o d 5 5 . 2 2 . As proven on a separate note, we can divide the terms by 2 2 to obtain 2 2 6 6 6 6 6 ≡ 2 2 y m o d 5 5 . Then, we apply the property of modulo arithmetic such that if a ≡ b m o d n , then k a ≡ k b m o d n for any integer k . With that, we know that 2 2 6 6 6 6 6 ≡ 2 2 y m o d 5 5 ⇒ 6 6 6 6 6 ≡ y m o d 5 5 . Take note that we do not use this technique on 2 6 6 6 6 6 6 6 ≡ 2 6 x m o d 5 6 so that we do not eliminate the 2 6 . Doing so would result in finding congruence for 5 6 and not 1 0 6 . Hence we have: 2 6 6 6 6 6 6 6 ( m o d 5 5 . 2 2 ) ≡ 2 6 x m o d 5 6 ⇒ 2 6 6 6 6 6 6 6 ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 Repeating this steps above (indicated with ** )over and over again, we eventually get: 2 6 6 6 6 6 6 6 ( m o d 5 ) ( m o d 5 2 ) ( m o d 5 3 ) ( m o d 5 4 ) ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 Then, we shall solve this step by step: 2 6 6 6 6 6 6 1 ( m o d 5 2 ) ( m o d 5 3 ) ( m o d 5 4 ) ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 2 6 6 6 6 6 6 ( m o d 5 3 ) ( m o d 5 4 ) ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 2 6 6 6 6 3 1 ( m o d 5 4 ) ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 2 6 6 6 5 3 1 ( m o d 5 5 ) ≡ 2 6 x m o d 5 6 2 6 6 1 1 5 6 ≡ 2 6 x m o d 5 6 ⇒ 2 1 1 5 0 . 3 1 1 5 6 ≡ 2 6 x m o d 5 6 Since 2 1 1 5 0 ≡ 5 3 7 4 m o d 5 6 and 3 1 1 5 6 ≡ 1 5 3 9 6 m o d 5 6 , we know that 2 1 1 5 0 . 3 1 1 5 6 ≡ 3 7 2 9 m o d 5 6 . Therefore, 2 6 x = 3 7 2 9 .
Finally, we compute our desired answer, x to be x = 3 7 2 9 × 2 6 = 2 3 8 6 5 6 . The 6 th digit from the right of 6 6 6 6 6 6 is 2 .
Proofs and workings used in solution
1 . If m ≡ n m o d k with g cd ( m , n , k ) = b , then b m ≡ b n m o d b k . This property is valid because by mathematical reasoning, if ( m − n ) divisible by k , then obviously b m − n is divisible by b k . Alternatively, we may also proof this by observing that since k m − n = z where z is an integer, then obviously k m − n = b k b m − n = z , and this completes the proof.
2 . Finding remainder when 6 4 divided by 5 3 . 6 4 ≡ 4 6 m o d 5 3 6 2 ≡ 3 6 m o d 5 3 So, 6 6 = 4 6 × 3 6 = 1 6 5 6 ≡ 3 1 m o d 5 3 .
3 . Similarly, finding remainder when 6 3 1 divide 5 4 . 6 4 ≡ 4 6 m o d 5 4 6 3 ≡ 2 1 6 m o d 5 4 Hence, 6 3 1 = ( 6 4 ) 7 × 6 3 ≡ 4 6 7 × 2 1 6 m o d 5 4 . Then, 4 6 2 ≡ 2 4 1 m o d 5 4 and hence, 6 3 1 ≡ 2 4 1 3 × 4 6 × 2 1 6 m o d 5 4 . 2 4 1 2 ≡ 5 8 1 m o d 5 4 6 3 1 ≡ 5 8 1 × 2 4 1 × 4 6 × 2 1 6 m o d 5 4 ⇒ 5 8 1 × 2 4 1 × 4 6 × 2 1 6 ≡ 5 3 1 m o d 5 4 ∴ 6 3 1 ≡ 5 3 1 m o d 5 4 Using these same steps as above, we can find 6 5 3 1 m o d 5 5 , 2 1 1 5 0 m o d 5 6 and 3 1 1 5 6 m o d 5 6 .